Induced Birefringence in 3D Printing: Concealing Information Optically within Printed Objects. Issue 8 (26th May 2022) - Roper, David M.; Kwon, Kyung‐Ah; Malone, Luke P.; Best, Serena M.; Cameron, Ruth E.
Abstract: This paper presents a novel method to spatially vary the intra‐layer birefringence of Fused Filament Fabricated (FFF) parts by controlling chain alignment during extrusion along individual rasters. The role of print speed, extrusion factor and layer separation on the birefringence of single PLLA layers is explored, at thicknesses ranging from 50–125 µm and print speeds 1000–6000 mm min −1 . The cumulative and subtractive effect of multiple PLLA layers are explored to elicit colours corresponding to a range of retardations, achieve complete extinction, and printing a physical Michel‐Levy chart. By increasing print speed and reducing layer separation and extrusion factor, a birefringence up to Δ n  = 9 × 10 −4 could be achieved in single layers. In multi‐layer structures, retardations of 0–800 nm are demonstrated. These results suggest that spatially varied birefringence can be used to store data, text or images, which can be resolved when parts are illuminated between polarizers. This effect is utilized to present a steganographic technique embedding information within bulk printed parts. These techniques might find application in a range of printed optics and devices, where spatial control over molecular alignment and associated influence on the propagation of light is desirable, including the ability to encode information within a print. Abstract : Using the novel development of spatially controllable induced alignment, a technique is presented to conceal information within 3D printed parts. The birefringence of printed layers is characterized in single and multilayer structures. Printing speed is employed to spatially control alignment, allowing the steganographic concealment of text and images through birefringence changes, revealed when structures are viewed between crossed polarizing filters.